Optimisation of ZnO Thin Films : Implants, Properties, and Device Fabrication - Nagar, Saurabh; Chakrabarti, Subhananda (Springer Singapore : Imprint: Springer, 2017)
This monograph describes the different implantation mechanisms which can be used to achieve strong, reliable and stable p-type ZnO thin films. The results will prove useful in the field of optoelectronics in the UV region. This book will prove useful to research scholars and professionals working on doping and implantation of ZnO thin films and subsequently fabricating optoelectronic devices. The first chapter of the monograph emphasises the importance of ZnO in the field of optoelectronics for ultraviolet (UV) region and also discusses the material, electronic and optical properties of ZnO. The book then goes on to discuss the optimization of pulsed laser deposited (PLD) ZnO thin films in order to make successful p-type films. This can enable achievement of high optical output required for high-efficiency devices. The book also discusses a hydrogen implantation study on the optimized films to confirm whether the implantation leads to improvement in the optimized results.